2023
DOI: 10.1039/d2qi02398a
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the pore space of a robust nickel–organic framework for efficient C2H2/C2H4 separation

Abstract: The separation of acetylene (C2H2) from ethylene (C2H4) is an important but challenging process in the industry because of their similar physical properties and kinetic molecular sizes. Here, we presented...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Simultaneously, the selectivity of C 2 H 2 /CO 2 is also calculated, taking into account that CO 2 serves as the primary impurity in acetylene production (Figure S10c). Apparently, the selectivity of JLU-Liu22 and JLU-Liu46 are comparable to previously reported adsorbent materials like BSF-1 under the same conditions, exceeding that of most reported high acetylene adsorption MOFs (Figure e). ,, It is worth noting that JLU-Liu46 showed the best performance in the separation and purification of acetylene. The phenomena can be mainly attributed to pore environment engineering, the urea group can sever as hydrogen bond acceptors to form multiple interactions, and the high-density OMSs can give π-interactions with C 2 H 2 (formation of metal–alkyne complexes), which is beneficial to its gas adsorption and separation.…”
Section: Resultssupporting
confidence: 70%
“…Simultaneously, the selectivity of C 2 H 2 /CO 2 is also calculated, taking into account that CO 2 serves as the primary impurity in acetylene production (Figure S10c). Apparently, the selectivity of JLU-Liu22 and JLU-Liu46 are comparable to previously reported adsorbent materials like BSF-1 under the same conditions, exceeding that of most reported high acetylene adsorption MOFs (Figure e). ,, It is worth noting that JLU-Liu46 showed the best performance in the separation and purification of acetylene. The phenomena can be mainly attributed to pore environment engineering, the urea group can sever as hydrogen bond acceptors to form multiple interactions, and the high-density OMSs can give π-interactions with C 2 H 2 (formation of metal–alkyne complexes), which is beneficial to its gas adsorption and separation.…”
Section: Resultssupporting
confidence: 70%
“…In addition, the cost and stability of MOFs are also important factors in practical applications. Some previous studies demonstrated that MOFs with size/shape-specific pores and suitable pore volume could be elaborately designed to achieve high adsorption selectivity and high working capacity in some separation processes. Besides the control of pore size and shape, another strategy to effectively and commonly improve the separation performance of MOFs is the introduction of organic functional groups and/or open metal sites (OMSs) to the pore surface of MOFs, which enhance the interactions between adsorbents and the guest molecules of interest. In view of this, the construction of stable nanoporous MOFs with functional pore surfaces through easily available organic ligands for the separation of hydrocarbons would be of great interest and importance. , …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have shown great potential in gas adsorption and separation due to their high surface area, modified pores, adjusted topological structure, and high adsorption capacity, as compared to traditional porous materials like zeolites and activated carbon. Several classic MOFs, including ZU-801, DUT-52, ZJU, , and DMOF, have exhibited excellent gas storage and separation performance. Researchers have made efforts to enhance gas adsorption and separation properties by functionalizing MOFs through the introduction of functional groups (−CH 3 , −NH 2 , −OH), tuning of pore size and the construction of open metal sites (OMSs). Previous studies have shown that providing an appropriate aromatic pore environment can enhance interactions between light hydrocarbon molecules and the MOF framework through dispersion and induction forces, a widely used and effective approach. , Our research group is committing to the engineering of pores to achieve efficient gas capture. ,,, In our work, we aim to introduce additional functional sites into the aromatic pore environment to achieve a synergistic effect from multiple adsorption sites.…”
Section: Introductionmentioning
confidence: 99%